2022
DOI: 10.1108/ijse-10-2021-0636
|View full text |Cite
|
Sign up to set email alerts
|

Probing the impact of cognitive heuristics on strategic decision-making during the COVID-19 pandemic: evidence from an emerging economy

Abstract: PurposeThis study aims to explore and clarify the mechanism by which cognitive heuristics influence strategic decision-making during the coronavirus disease 2019 (COVID-19) pandemic in an emerging economy.Design/methodology/approachData collection was conducted through a survey completed by 213 top-level managers from firms located in the twin cities of Pakistan. A convenient, purposively sampling technique and snowball method were used for data collection. To examine the relationship between cognitive heurist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…According to Ahmad et al (2022c), strategic planning is primarily the responsibility of company owners and top managers. Thus, to achieve the research objective, the sample of this study consists of owners and top managers of SMEs from the twin cities of Pakistan (Rawalpindi and Islamabad).…”
Section: Research Methodology 31 Sampling and Data Collectionmentioning
confidence: 99%
“…According to Ahmad et al (2022c), strategic planning is primarily the responsibility of company owners and top managers. Thus, to achieve the research objective, the sample of this study consists of owners and top managers of SMEs from the twin cities of Pakistan (Rawalpindi and Islamabad).…”
Section: Research Methodology 31 Sampling and Data Collectionmentioning
confidence: 99%
“…Since most of the people in slums aren't aware of social welfare schemes and also they were hesitant to respond to our queries; as a result, we employed the snowball sampling technique (Ahmad et al. , 2022; Singh et al.…”
Section: Methodsmentioning
confidence: 99%
“…Since most of the people in slums aren't aware of social welfare schemes and also they were hesitant to respond to our queries; as a result, we employed the snowball sampling technique (Ahmad et al, 2022;Singh et al, , 2021 to collect the primary data for the study as it was appropriate and convenient for us to reach beneficiaries through the references from concerned peer groups, bank branches and NGO's (Table 2).…”
Section: Data Collectionmentioning
confidence: 99%
“…Adielyani and Mawardi (2020) discovered that herding behavior, risk tolerance and overconfidence all have a significant positive affect on stock investment decisions. The paper by Ahmad et al (2021b, 2022a) indicates that recognition-based heuristic biases, like name memorability, alphabetical order and name fluency, have a significant positive impact on individual investors’ decision-making and a negative effect on their investments’ performance. From an economic point of view, these results suggest that individual investors with recognition heuristic-driven biases generate high trading volumes on the stock market, which negatively impact their investment performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Their study found that heuristic-driven biases, such as overconfidence, representativeness, availability, anchoring and adjustment, have a significant and detrimental impact on the strategic decisions made by entrepreneurs operating in emerging markets. According to Ahmad et al (2022aAhmad et al ( , 2022b, strategic decision-making is quite complex, necessitating extensive brainstorming. Most strategic decision-makers use cognitive heuristics, such as the disposition effect, self-attribution and underconfidence, in attempting to avoid risky losses in uncertain situations like COVID-19, resulting in judgmental errors.…”
Section: Introductionmentioning
confidence: 99%